SIMULASI PENGENDALIAN ROUTER MIKROTIK MENGGUNAKAN ANDROID - Risaldi, Moh; Ayuningtyas, Astika (Compiler, 2018)
Userman is a tool in mikrotic that serves as a network user. Userman's tools are only accessible by admin and can only be accessed via a computer device. Utilization of handheld or mobile phone device at this time the usual thing because cellular phone or handphone is as companion in carrying out everyday activities. That's what makes Hanphone is very commonplace for some people. This is because some Mobile already has the function and ability more than just the basic function. Android as an operating system that can be embedded in mobile devices have the ability to be installed applications required by the user. In this final project, the mikrotik application can be used to manage the admin that has been in the menu of user management and mikrotik application can also be successful to monitor network traffic and limit the bandwidth to the connected user.